Cost and profit efficiency of MENA banking sector: Influence of structural factors - AYACHI, Kaïs; GASSOUMA, MOHAMED SADOK; CHICHTI, JAMELEDDINE (Bankers, Markets & Investors, 2019)
This paper aims to provide empirical evidence on the impact of different endogenous and exogenous factors as well as the 2011 Arab Revolution effect on bank efficiency in terms of cost and profit in the MENA region, taking into account the difference in economic development level between the selected countries. We have conducted a cross-country analysis requiring that factors specific to the various selected countries such as macroeconomic conditions, market structure, financial development, capital openness, Bank risk-taking, regulatory measures, institutional quality, and deposit insurance system be taken into consideration. In order to properly carry out our empirical investigation, we have opted for the methodology put forward by Battese & Coelli (1995). Our analysis is conducted through the application of data related to a sample of 198 commercial banks operating in 10 MENA countries between 2000 and 2014. The main results of our research show that the mean cost efficiency is far more important than profit efficiency (82.52% as against 44.96%) and the Arab Revolution has only an effect on countries affected by this event leading to a fall of cost efficiency and convex form of profit efficiency. In addition, we notice that bank inefficiency in high and middle-income countries can be managed by capital openness, market concentration, inflation, inter-banking interest rate, market concentration, economic growth and good institutional quality. In contrast, market discipline driven by private control and monetary policy provided by government interest rate on bond yield can solve inefficiency only in the high-income countries.